2001
DOI: 10.1074/jbc.m010417200
|View full text |Cite
|
Sign up to set email alerts
|

A Macrophage Protein, Ym1, Transiently Expressed during Inflammation Is a Novel Mammalian Lectin

Abstract: Oral infections of mice with 2؉ and Mg 2؉ ion-independent. The binding avidity of Ym1 to GlcN oligosaccharides was enhanced by more than 1000-fold due to the clustering effect. Specific binding of Ym1 to heparin suggests that heparin/heparan sulfate may be its physiological ligand in vivo during inflammation and/or tissue remodeling. Although it shares ϳ30% homology with microbial chitinases, no chitinase activity was found associated with Ym1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
238
0
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(249 citation statements)
references
References 74 publications
10
238
0
1
Order By: Relevance
“…This would be in some analogy with the proposed contribution of HSPGs to amyloid formation (Stevens and Kisilevsky, 2000). (Chang et al, 2001) and intracellular crystalline bodies in vivo (Nio et al, 2004), in particular in alveolar macrophages from aged immunodeficient mice (Guo et al, 2000;Harbord et al, 2002). Secondly, since HS and heparin are physiological ligands to Ym1 (Chang et al, 2001), it may be speculated that changes in HS turnover affect Ym1 aggregation and crystallization.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…This would be in some analogy with the proposed contribution of HSPGs to amyloid formation (Stevens and Kisilevsky, 2000). (Chang et al, 2001) and intracellular crystalline bodies in vivo (Nio et al, 2004), in particular in alveolar macrophages from aged immunodeficient mice (Guo et al, 2000;Harbord et al, 2002). Secondly, since HS and heparin are physiological ligands to Ym1 (Chang et al, 2001), it may be speculated that changes in HS turnover affect Ym1 aggregation and crystallization.…”
Section: Discussionmentioning
confidence: 72%
“…Alveolar macrophages constitutively express Ym1, a chitinase-like protein that previously has been demonstrated to exhibit a marked tendency to spontaneously form crystals in vitro (Chang et al, 2001). Moreover, Ym1 is known to form needle-shaped intracellular crystals (Harbord et al, 2002;Nio et al, 2004) that closely resemble the crystals found in Hpse -/-alveolar macrophages (Fig.…”
Section: Accumulation Of Ym1 In Alveolar Macrophages From Hpse -/-Micementioning
confidence: 84%
See 1 more Smart Citation
“…p21 is a p53 target gene, implicated in cell cycle arrest, tumor suppression and used as a marker of cellular senescence (Serrano et al ., 1997). Interestingly, genes previously reported in activated microglia such as Egr‐1, CCl3, Chi3l3, Chi3l4, and Lyz1 (McMahon & Monroe, 1996; Chang et al ., 2001; Babcock et al ., 2003; Friedle et al ., 2011) and in proliferation such as Fos, Jun, and Mapk8 (Yamasaki et al ., 2014) were found to be mildly but significantly downregulated in G4 mTerc −/− microglia.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, AAM and/or YM1 are involved in eosinophil chemotaxis and might stimulate the migration of cells to parasites [27,28]. Induced AAM and YM1 have been shown in both mice and guinea pigs infected with T. spiralis [29,30].…”
Section: Eosinophil Migration and Infiltration To Tissuesmentioning
confidence: 99%